Robot-assisted percutaneous screw fixation in the treatment of navicular fracture - Wang, Cheng; Fu, Shaoling; Li, Xueqian; Wang, Jiazheng; Wu, Chenglin; Zhang, Jieyuan; Song, Guoxun; Gu, Wenqi; Shi, Zhongmin (Frontiers in Surgery, 2023)
Background: Open reduction and internal fixation (ORIF) for tarsal navicular fractures may lead to incision infection and limited joint mobility. The use of intraoperative robot, minimally invasive closed reduction and internal fixation can better reduce the fracture and allow for early exercise training. The purpose of the study was to investigate the feasibility of robot-assisted percutaneous screw internal fixation robot-assisted in the treatment of navicular fracture. Methods: From June 2019 to December 2021, 27 patients with navicular fracture were treated with surgical treatment. Among them, 7 cases were treated with robot-assisted percutaneous screw internal fixation, and 20 cases were treated with open reduction and internal fixation (ORIF). Outcomes and function were compared according to the visual analogue scale (VAS) and the American Orthopaedic Foot and Ankle Surgical Society ankle-hindfoot score (AOFAS-AH) at last follow-up. Results: The operation of 27 patients was successful, only one attempt was required in the 7 cases of robot-assisted percutaneous guide wire insertion and screw placement, intraoperative fluoroscopy showed that the depth of the implant was appropriate, the position of the implant was satisfactory. Cutaneous nerve injury occurred in 2 patients in ORIF group, and no other complications such as wound infection, delayed healing and internal fixation failure occurred. According to the VAS score and AOFAS score at the last follow-up, the AOFAS score and the VAS score of the robot-assisted navigation percutaneous screw fixation group was 92.25±2.22 and 0.75±0.25 respectively, and the AOFAS score and the VAS score of the ORIF group was 82.25±7.15 and 0.50±0.29 respectively. Postoperative reexamination of the fracture site of the patients healed well. Conclusion: Tarsal navicular fractures have unique characteristics and are prone to a series of complications. Intraoperative robot-assisted percutaneous internal fixation for tarsal navicular fracture can achieve precise location of fracture site on the basis of minimally invasive treatment. The current view is that this procedure has fewer complications, faster postoperative recovery, and higher patient satisfaction.